LNC473 Regulating APAF1 IRES-Dependent Translation via Competitive Sponging miR574 and miR15b: Implications in Colorectal Cancer - Huizhe Wu; Xiaoyun Hu; Yalun Li; Qiuchen Chen; Tong Sun; Yun Qiao; Wenyan Qin; Zhikun Wu; Boshi Fu; Haishan Zhao; Rui Zhang; Minjie Wei (Elsevier, 2020)
A growing number of studies have focused on the involvement of non-coding RNAs (ncRNAs) in the internal ribosome entry site (IRES)-mediated translation in tumorigenesis; however, the underlying mechanisms in colorectal cancer (CRC) remain elusive. In this study, we show that LINC00473 (LNC473) exerted its functions as a tumor suppressor in promoting apoptotic protease-activating factor 1 (APAF1) IRES activity through competitively sponging miR574-5p and miR15b-5p in CRC initiation and pathogenesis. Specifically, LNC473 and its downstream target APAF1 were significantly downregulated accompanied by upregulated miR574-5p and miR15b-5p in CRC cells and tissues, which had a significant prognostic impact on clinical outcomes in our CRC cohort (n = 157). Furthermore, ectopic LNC473 significantly sponged endogenous miR574-5p or miR15b-5p and thereby inhibited cell proliferation and colony formation capacity, and it accelerated cell apoptosis through activating the APAF1-CASP9-CASP3 pathway. Notably, LNC473 overexpression resulted in dramatic promotion of APAF1 IRES activity and translation, whereas rescue experiments confirmed the recovery by the existence of LNC473 and miR574/15b-5p. Mechanistically, LNC473 overexpression promoted IRES binding domain exposure and removed the constraints controlling from miR574-5p and miR15b-5p, and subsequently enhanced IRES-mediated APAF1 expression in vitro and in vivo. Therefore, our results uncover a novel LNC473-miR574/miR15b-APAF1 signaling axis, which provides new targets and crosstalk regulation mechanism for CRC prevention and treatment.